Using Shattered Assumption Theory to Understand How Cyberbullying Victimization is Linked With Perceived Control Among Chinese College Students - Wang, Hongxia (Journal of interpersonal violence, 2022)
Perceived control (PC) is considered as one of the most basic psychological needs of human beings, and it is also an important index to measure individual mental health. Previous studies have shown that negative life experience is an important risk factor for predicting PC. With the prevalence of cyberbullying among college students, this study explored how cybervictimization (CV) was related to the PC, mediated through the personal belief in a just world (PBJW). Besides, this study examined the moderating role of interpersonal forgiveness (IF) in the direct relationship between CV and PC and the indirect connection through PBJW. It was expected that CV would negatively predict the PC, and the PBJW would mediate this relationship. The direct and indirect effects were stronger in individuals with low IF than those with high IF. In this study, 837 Chinese college students were invited to conduct an online survey using a convenient sampling method. Participants were asked to complete the measurement of CV, PBJW, IF, and PC. After controlling gender and age, the results revealed that CV could directly and negatively predict college students? PC and indirectly predict the PC through the mediation of PBJW. Additionally, IF moderated the effect of CV on PBJW and PC. Unlike what we expected, the effect of CV on PBJW was stronger for low IF individuals than those with high IF, while the effect of CV on PC was stronger for high IF individuals than those with low IF. The unexpected orientation and other results were discussed.